ICT Innovation for Industry 4.0 Solutions - Atijah Marsithi; Azrin Azli Suhaimi; Mohd Helmy Abd Wahab; Radzi Ambar (2023)
The writing of the chapters in the book entitled ICT Innovation for Industry 4.0 Solutions came from the Technical Report of the Final Project Student Semester 5 December Session 2019, Diploma in Information Technology (Digital Technology), Department of Information and Communication Technology, Politeknik Muadzam Shah. This book consists of 10 chapters and the production of chapters in this book is an initiative implemented by the department in providing exposure to students in scholarly writing. This exposure is expected to cultivate their interest in research and publication activities.